River Runoff as a Major Driver of Anchovy (Engraulis ringens) Recruitment but Not of Common Sardine (Strangomera bentincki) in Central-South Chile - Zunguza, Afonso; Montes, Rodrigo M.; Cubillos, Luis A.; Quiñones, Renato A. (Frontiers in Marine Science, 2022)
River runoff to the coastal zone is one of the most important environmental variables that influences the structure and functioning of the neritic trophic web and modulates temporal fluctuations of coastal fishery production in many ecosystems worldwide. The relationship between recruitment of anchovy (Engraulis ringens) and common sardine (Strangomera bentincki) in central-south Chile (34º-40ºS) and fluctuations in river runoff was analyzed during the last two decades (1999-2018) using linear and nonlinear regression models. River runoff was also incorporated as a co-variate in Beverton-Holt (BH) stock-recruitment models. Anchovy recruitment was found to be positive and significantly associated with river runoff for all analyzed rivers both for the runoff calculated during its main reproductive period (July-October) and for each single month during this period. This detected nonlinear relationship remained significant when runoff was analyzed for the central macrozone (CMZ) and southern macrozone (SMZ). In contrast, no relationship between runoff and recruitment was detected for the common sardine in any river or macrozone (CMZ, SMZ), for each month of the main reproductive season or for the whole reproductive period (July-October). No density-dependent regulation was detected using BH stock-recruitment models for either species, with or without total freshwater input (i.e. the joint discharge of all rivers; RIVSUM index) as a covariate. Our results highlight the relevance of river runoff as a major driving factor in anchovy recruitment variability, suggesting that high (low) monthly runoff anomalies during the main reproductive period of anchovy populations markedly affect the survival of its early stages, altering recruitment success. For common sardine the runoff effect was not significant, which suggests that other oceanographic/climatic factors (wind-driven upwelling, sea surface temperature, El Niño) are more relevant in driving the variability of its recruitment than river runoff.